Current Issues of Diagnosis and Treatment of Functional Gastrointestinal Disorders in Children - Marika I. Broeva; Andrei N. Surkov; Vladislav V. Chernikov (Union of pediatricians of Russia, 2018)
The analysis of the prevalence, clinical manifestations, diagnosis, and treatment of functional gastrointestinal disorders (FGID) in  infants was carried out. According to the analysis results the  development of FGID in infancy is caused by disorders of motor function and somatic sensitivity of the digestive organs,  changes in the secretory and suction functions of this system, largely due to anatomophysiological features of an early age. The  peculiarities of posseting, colic, and constipation are considered as  the most frequent FGID manifestations in infants. The current  approaches to the treatment of the specified manifestations are  analyzed, including a number of activities, in particular, psychological preparation of parents, support of breastfeeding, rational nutrition of the mother during breastfeeding, if necessary, the selection of  formulas for mixed or artificial feeding, the use of medicines and probiotics. We noted that the high incidence and adverse effects  of FGID in children determine the urgency to research on the mechanisms of their development in order to improve preventive and curative interventions.